Utility of point-of-care ultrasound of the liver in the neonatal intensive care unit: experience from a case series - Sohane, Arpit; Deshpande, Sujata; Nagpal, Rema; Singh, Yogen; Suryawanshi, Pradeep (Frontiers in Pediatrics, 2025)
IntroductionPoint-of-care ultrasound (POCUS) is increasingly being utilized for the management of sick and premature neonates in the neonatal intensive care unit (NICU). While neonatologist-performed cranial, lung, and cardiac ultrasound have become the standard of care in many NICUs across the world, the use of POCUS for the evaluation of the liver remains relatively unexplored.Materials and methodsThis case series included neonates admitted to a tertiary-care NICU between January 2021 and April 2025, with radiological liver abnormalities detected on point-of-care ultrasound by treating neonatal physicians. Cases were identified from stored ultrasound images, and clinical data were extracted from electronic and physical medical records.ResultsSix patients were identified, in whom a liver POCUS performed by the treating physician revealed a radiological liver abnormality for presenting symptoms that did not include cholestasis or deranged liver function tests. The conditions diagnosed included liver hemangioma, total anomalous pulmonary venous connection, liver hematoma, hepatic abscess, hepatic total parenteral nutrition extravasation, and portal vein thrombosis.ConclusionThis case series demonstrates the significant role of liver POCUS for the diagnosis of various conditions in neonates, which may be hematological, cardiac, infectious, hemorrhagic, or iatrogenic in origin. Incorporation of liver POCUS into NICU protocols for screening symptomatic infants, particularly those with umbilical venous catheters, pulmonary hypertension, congestive cardiac failure, or unexplained deterioration, may expedite early diagnosis and management of such conditions.